Prototype of Temperature and Humidity Control and Monitoring System in 20 Kv Cubicles Using IoT-Based PID Control - Satryo Budi Utomo; Widyono Hadi; Arkan Bari Amanullah; Gamma Aditya Rahardi; Zulfa Fahrunnisa; Dananjaya Endi Pratama (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2026)
Cubicles are key parts of electrical power distribution systems. They control, connect, and protect equipment to ensure electricity is delivered safely and efficiently. However, poor regulation of temperature and humidity in medium-voltage cubicles (20 kV) can trigger corona discharge, leading to power losses, insulation degradation, and reduced operational reliability. This study presents the design and implementation of an Internet of Things (IoT)-based automatic control system for maintaining optimal environmental conditions inside cubicles. The system integrates an ESP32 microcontroller, a DHT22 sensor for temperature and humidity measurement, a KY-037 sound sensor for detecting corona discharge, a Positive Temperature Coefficient (PTC) heater, and an exhaust fan. A Proportional-Integral-Derivative (PID) control algorithm adaptively regulates heater and fan operation based on sensor feedback. Real-time monitoring and control are achieved via a Firebase cloud database and a custom mobile application developed with MIT App Inventor. Experimental results show that the system maintains humidity stability within 64%–72% relative humidity, improving energy efficiency and effectively preventing corona discharge conditions. The proposed system enhances operational reliability and extends the service life of cubicle installations in medium-voltage applications.